2018
DOI: 10.1016/j.ebiom.2018.11.037
|View full text |Cite
|
Sign up to set email alerts
|

The heat shock protein amplifier arimoclomol improves refolding, maturation and lysosomal activity of glucocerebrosidase

Abstract: BackgroundGaucher Disease is caused by mutations of the GBA gene which encodes the lysosomal enzyme acid beta-glucosidase (GCase). GBA mutations commonly affect GCase function by perturbing its protein homeostasis rather than its catalytic activity. Heat shock proteins are well known cytoprotective molecules with functions in protein homeostasis and lysosomal function and their manipulation has been suggested as a potential therapeutic strategy for GD. The investigational drug arimoclomol, which is in phase II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 64 publications
(99 reference statements)
2
28
0
Order By: Relevance
“…No clear ultrastructural defects could be demonstrated in nasal brushes and semen sample however. Remarkably, heterozygous carriers of the missense variant displayed an intermediate cellular phenotype, a feature that has already been described both in ciliary and nonciliary contexts (Fog et al, 2018; Noone et al, 2004). Downstream analysis of the Sonic Hedgehog (SHH) signaling pathway was not informative under the given experimental setup (data not shown).…”
Section: Discussionsupporting
confidence: 54%
“…No clear ultrastructural defects could be demonstrated in nasal brushes and semen sample however. Remarkably, heterozygous carriers of the missense variant displayed an intermediate cellular phenotype, a feature that has already been described both in ciliary and nonciliary contexts (Fog et al, 2018; Noone et al, 2004). Downstream analysis of the Sonic Hedgehog (SHH) signaling pathway was not informative under the given experimental setup (data not shown).…”
Section: Discussionsupporting
confidence: 54%
“…Recently, a group demonstrated a slow release system for ambroxol (Enshaei et al, 2019). Another, interesting recent finding is that Arimoclomol, a heat shock protein amplifier has been shown to increase levels of GCase and GCase activity in GD models (Fog et al, 2018). Therefore, our first study supports the claim that GCase modulation can be a useful treatment for PD and indicates that chaperone therapy enabling correct folding and trafficking of GCase is a promising approach.…”
Section: Concluding Remarks and Future Perspectivessupporting
confidence: 68%
“…Arimoclomol is an aromatic heteromonocyclic compound that underwent clinical trial phase 3 for Amyotrophic Lateral Sclerosis [92]. It rescues glucocerebrosidase in fibroblasts of Gaucher patients both in terms of quantity and in terms of maturation [93] and prevents aggregation of a missense mutant of rhodopsin, P23H, which is frequently encountered in retinitis pigmentosa [94]. Kelly et al [95] suggested that co-administration of a proteostasis regulator and of pharmacological chaperone could have a synergistic effect on rescuing missense pathogenic mutants.…”
Section: Other "Small Molecules": Alternative or Synergistic Approachmentioning
confidence: 99%